2 <tex Notation="TeX">$×$</tex> 80 Gbit/s DWDM Bidirectional Wavelength Reuse Optical Wireless Transmission - Hai-Yin Hsu; Wan Chian Lu; Hoa Le Minh; Zabih Ghassemlooy; Yi-Lin Yu; Shien-Kuei Liaw (IEEE Photonics Journal, 2013)
We demonstrate a practical 2×80 Gbit/s dense wavelength division multiplexing (DWDM) bidirectional short-range optical wireless link. The measured power penalties for the bidirectional transmission are less than 0.8 and 0.2 dB compared to the back-to-back link and the unidirectional transmission system, respectively. We also practically evaluate the impact of the offset angles between the optical transmission path and the building windows. The result shows that the power penalty is as small as 0.3 dB. This technology offers a great potential for applications in building-to-building inter-transmission as part of local/wide area networks.